UPAYA PENINGKATAN KEMAMPUAN MATEMATIKA SISWA MELALUI PENERAPAN PENDEKATAN PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK DI KELAS I SD NEGERI 24 BENGKULU SELATAN TAHUN PELAJARAN 2014/2015 - Ijariah Ijariah (PAKAR Pendidikan, 2016)
This research is a type of classroom action research in which researchers directly involved in the research to guide and facilitate students in learning activities that are implemented through teaching and learning in schools. The main purpose of this action research is to determine the application-based learning approach to realistic mathematics education in an effort to improve students' understanding in operationalising addition and subtraction of numbers 1 to 20 in the first grade students in elementary school students of State Elementary School 24 South Bengkulu good and effective at the Academic Year 2014/2015. Based on the research results it can be concluded that prasiklus activity obtained from the average value of 52.31 students increased to 66.92 in the first cycle, after learning method is done by using a learning approach based on realistic mathematics education optimally then the average value of students to 89 , 23 in the second cycle. Researchers found the use of realistic mathematics education learning approach is very relevant and effective for improving math skills in elementary school students. Thus application-based learning approach optimally realistic mathematics education at State Elementary School 24 South Bengkulu in general can improve the quality of learning of mathematics.